2022
DOI: 10.1038/s41590-022-01329-5
|View full text |Cite
|
Sign up to set email alerts
|

Pan-vaccine analysis reveals innate immune endotypes predictive of antibody responses to vaccination

Abstract: Several studies have shown that the pre-vaccination immune state is associated with the antibody response to vaccination. However, the generalizability and mechanisms that underlie this association remain poorly defined. Here, we sought to identify a common pre-vaccination signature and mechanisms that could predict the immune response across 13 different vaccines. Analysis of blood transcriptional profiles across studies revealed three distinct pre-vaccination endotypes, characterized by the differential expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 45 publications
(76 reference statements)
4
47
1
Order By: Relevance
“…Overall, Fourati et al 2 and Hagan et al 4 have demonstrated the use of this compendium as a highly valuable tool to gain insight into the variation in antibody response observed between individuals, which provides an excellent resource for immunologists and vaccinologists to use in comparative studies to obtain further mechanistic insight into the effect of genetic factors (age, sex, ethnicity) and environmental factors (nutrition, geographical location, time of vaccination) that shape cellular and molecular mechanisms and underpin antibody responsiveness. Growing evidence points to adult females having better protective immune responses 9 , possibly due to increased innate immune responses; to pregnant women responding better to vaccination in the first and third trimesters; 10 to novel mRNA vaccines inducing a more potent monocyte response; 11 and to greater effectiveness of vaccination in the morning because of circadian rhythms 12 .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, Fourati et al 2 and Hagan et al 4 have demonstrated the use of this compendium as a highly valuable tool to gain insight into the variation in antibody response observed between individuals, which provides an excellent resource for immunologists and vaccinologists to use in comparative studies to obtain further mechanistic insight into the effect of genetic factors (age, sex, ethnicity) and environmental factors (nutrition, geographical location, time of vaccination) that shape cellular and molecular mechanisms and underpin antibody responsiveness. Growing evidence points to adult females having better protective immune responses 9 , possibly due to increased innate immune responses; to pregnant women responding better to vaccination in the first and third trimesters; 10 to novel mRNA vaccines inducing a more potent monocyte response; 11 and to greater effectiveness of vaccination in the morning because of circadian rhythms 12 .…”
mentioning
confidence: 93%
“…Using unsupervised clustering analysis of blood transcriptional modules previously coupled to immunological function 1 , Fourati et al classified pre-vaccination transcriptional profiles into three main endotypes 2 . Contributing to 12% of the variance observed in healthy participants, these endotypes were differentially defined by the expression of blood modules associated with innate immune responses, including Toll-like receptor (TLR) genes, interferon-mediated genes and genes associated with metabolic alterations downstream of the transcription factor NF-κB, that were critical for antiviral responses, antigen presentation and B cell activation.…”
mentioning
confidence: 99%
“…Such studies have used unbiased immune profiling to identify signatures of response to perturbations and predictors of outcomes such as antibody response to vaccination [6][7][8][9][10][11][12][13][14] , uncovering contributions from intrinsic factors, such as genetics 15 , age 16,17 , and sex 18 . Furthermore, accumulating evidence from these studies supports the hypothesis that immune system status prior to a perturbation can predict and potentially influence both response quality and quantity 6,16,[19][20][21][22][23] . For example, we identified transcriptome signatures reflective of an immune system "set point" predictive of higher antibody response following vaccination in healthy individuals 22 ; the same signature when evaluated during relative clinical quiescence was also linked to increased plasma cell related transcriptomic activity during disease flares in lupus patients.…”
Section: Introductionmentioning
confidence: 70%
“…Further complicating the study of correlates of protection against influenza is the substantial degree of baseline immune variation that exists across humans, which is now recognized as a key determinant in predicting efficacy of some vaccines and therapeutics, and modeling disease outcomes [14][15][16][17][18] . Differences in host genetics, environmental and demographic factors, and antigen exposure histories impact the composition of baseline innate, cellular, and humoral compartments, and may augment differing responses to influenza virus infection or vaccination 17,[19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%